2014
DOI: 10.1136/jclinpath-2014-202320
|View full text |Cite
|
Sign up to set email alerts
|

p-mTOR expression is associated with better prognosis in luminal breast carcinoma

Abstract: p-mTOR expression is associated with smaller, lower-grade and with luminal BC. In multivariable analysis, p-mTOR expression was associated with longer DFS and OS, independently of the size, grade and lymph node status, especially in luminal BCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
3
6
0
Order By: Relevance
“…It has been shown that AKT hyperactivation could induce endocrine resistance in breast cancer and non-small-cell lung cancer 1015. We also showed AKT hyperphosphorylation in PRCs with MPA treatment (Figures 2 and 3).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It has been shown that AKT hyperactivation could induce endocrine resistance in breast cancer and non-small-cell lung cancer 1015. We also showed AKT hyperphosphorylation in PRCs with MPA treatment (Figures 2 and 3).…”
Section: Discussionsupporting
confidence: 62%
“…Aberrant hyperactivation of PI3K/AKT/mTOR pathway is one of the most common tumor-related signaling pathways that can be detected in a variety of tumor types, such as breast cancer, colorectal cancer, endometrial carcinoma, lung cancer, and glioblastoma, mainly including PIK3CA mutation, PTEN loss, and AKT1 mutation. In addition, KRAS mutation and BRAF mutation from the MAPK pathway can also result in PI3K/AKT/mTOR pathway activation 1015. A previous study showed that progestin might activate PI3K/AKT signaling pathway independent of progesterone receptor (PR) in breast cancer 16…”
Section: Introductionmentioning
confidence: 99%
“…Five [22–26, 29], three [24, 27, 28], and three [22, 28, 30]studies reported the HR and 95% CI for DFS, OS, and RFS, respectively. The results of the meta-analysis are shown in Figs 2–4.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the clinical relevance of hyperactive Akt/mTOR depends on the tumor type. Two recent meta‐analyses revealed that hyperactive mTOR is associated with worse prognosis in gynecologic and gastrointestinal cancers, whereas it is associated with good prognosis in some breast cancer types or in lung cancer . Although, García–Carracedo et al reported mTOR activation was correlated with improved clinical outcome in patients with laryngeal carcinomas.…”
Section: Discussionmentioning
confidence: 99%